Understanding receptivity to interruptions in mobile human-computer interaction - Fischer, Joel (2011)
Interruptions have a profound impact on our attentional orientation in everyday life. Recent advances in mobile information technology increase the number of potentially disruptive notifications on mobile devices by an increasing availability of services. Understanding the contextual intricacies that make us receptive to these interruptions is paramount to devising technology that supports interruption management.